Respuesta :
The answer is:
y = x² + 3x + 1
y = 2x² + 2x + 3
If a = b = y, then a = y and b = ?
Our expression is x² + 3x + 1 = 2x² + 2x + 3
Let x² + 3x + 1 = 2x² + 2x + 3 = y
Therefore
x² + 3x + 1 = y
2x² + 2x + 3 = y
Now we have the system of two equations:
1. y = x² + 3x + 1
2. y = 2x² + 2x + 3
y = x² + 3x + 1
y = 2x² + 2x + 3
If a = b = y, then a = y and b = ?
Our expression is x² + 3x + 1 = 2x² + 2x + 3
Let x² + 3x + 1 = 2x² + 2x + 3 = y
Therefore
x² + 3x + 1 = y
2x² + 2x + 3 = y
Now we have the system of two equations:
1. y = x² + 3x + 1
2. y = 2x² + 2x + 3
Answer:
the answer to this question is
y = x² + 3x + 1
y = 2x² + 2x + 3